Penguatan dan Pendampingan Pelayanan Kesehatan Berbasis Pklt Poltekkes Kemenkes Bengkulu sebagai Implementasi IPE dan IPC - Darwis; Dino Sumaryuno; Kamsiah; Avrilya Iqoranny Susilo; Lusi Andi Andriani (Syntax Corporation, 2023)
Integrated health services are one of the methods that are easier to develop, especially with the IPE and IPC approaches in basic and comprehensive plenary health services in the field of health at the age level which include health improvement, prevention, treatment. This community service activity is carried out in conjunction with PKLT. The purpose of this activity is to provide learning experiences to students in real life in the community and contribute to health services, including the introduction of health problems, mobilizing community participation. This KKN activity is carried out for 18 effective days, from January 16 to January 28, 2023, students are in workshops during the activity. The focus of activities in the RT 2 to RT 10 puskesmas area includes the working area of the Anggut Atas Health Center, Anggut Atas Village, Gading Cempaka District, Bengkulu City. The form of activity uses the method of jumping directly and being around residents. Activities are divided into three stages including the Preparation, Implementation and Evaluation stages. prevention and provision of hypertension, DM, rheumatism in the form of STBM, garbage disposal, composting of Posbindu activities, Posyandu, family planning services through individual group counseling and Door to Door activities, demonstrations and simulations of elderly subjects, mothers of toddlers, adolescents and community leaders in particular, 28 elderly people, 15 people with hypertension, 9 people with DM, 8 people with high cholesterol, 15 families who do not have healthy latrines, 15 couples of childbearing age who have not had 15 pairs of contraceptives. It is hoped that the puskesmas can continue to be active in improving the degree of public health in the Anggut Atas Village area. It is expected that cross-program and sectoral cooperation will always provide support and direction to the community in improving health status